Building the minimum wage: Germany's first sectoral minimum wage and its impact on wages in the construction industry - Pia Rattenhuber (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The very first minimum wage in Germany was introduced in 1997 for blue-collar workers in sub-sectors of the construction industry. In the setting of a natural experiment blue-collar workers in neighboring 4-digit-industries and white-collar workers are used as control groups for differences-in-differences-in-differences estimation based on linked employer-employee data. Estimation results reveal a sizable positive average impact on wages in East Germany and no effect in West Germany. Size and significance of effects are not homogeneous across wage regimes (individual vs. collective contracts) and across the distribution suggesting spillover effects to wages where the minimum is not binding.
Keywords: C21; J18; J38; 330; minimum wage; construction sector; linked employer-employee data; differences-in-differences-in-differences; unconditional quantile regression